Offensive playing profiles of football teams from the 1999 Women's World Cup Finals - Konstadinidou, X.; Tsigilis, N. (International Journal of Performance Analysis in Sport, 2005)
The present study was designed to examine the offensive tactic of elite women's football teams. The sample of the study constituted of 20 games of the four top(quarter finalists) teams of the 3rd Women's World Cup (USA, China, Brazil, Norway). Totally, 749 offensive phases were analyzed. Teams' offensive patterns during games were coded using the following categories: (1) team, (2) zone of scoring attempt, (3) source of scoring attempt, (4) ball possession and (5) type of passes. Correspondence analysis showed that the four teams had different offensive profile. USA's scoring attempts were mainly executed from the central zones using combinations of small and medium passes with low possession and set plays. China's scoring attempts were mainly performed from the central and left zone after a combination of two or three small and intermediate passes. The source of Brazil's scoring attempts was frequently executed from the box area and the right offensive zone, using combination with small passes and individual actions. The source of Norway's final scoring attempts was mainly crosses and opponents mistake, executed from the box area. In addition, Norway frequently used small possession with long balls beginning from the defend area directed to the opponents' box area.